2019
DOI: 10.1186/s13578-019-0275-1
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of Tim-3 mediated autophagy in chronic stress induced immunosuppression

Abstract: BackgroundPsychological and physical stress can either enhance or suppress immune functions depending on a variety of factors such as duration and severity of stressful situation. Chronic stress exerts a significantly suppressive effect on immune functions. However, the mechanisms responsible for this phenomenon remain to be elucidated. Autophagy plays an essential role in modulating cellular homeostasis and immune responses. However, it is not known yet whether autophagy contributes to chronic stress-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Inflammation mediators can disrupt the clearance of misfolded proteins. To the contrary, the impaired autophagy causes inflammation [46]. We found that the lysosomal functional protein, represented by the expression of RAB7 and LAMP1 were decreased in the stressed microglia, while RAGE −/− in microglia reversed this effect and increased the acidity of lysosome.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Inflammation mediators can disrupt the clearance of misfolded proteins. To the contrary, the impaired autophagy causes inflammation [46]. We found that the lysosomal functional protein, represented by the expression of RAB7 and LAMP1 were decreased in the stressed microglia, while RAGE −/− in microglia reversed this effect and increased the acidity of lysosome.…”
Section: Discussionmentioning
confidence: 77%
“…Evidences show psychological and physical stress can either enhance or suppress immune responses depending on a variety of factors such as duration and severity of stressful situation. Mitophagy flux involves the activation, inflammatory response, and survival of microglia [46,47]; however, the detailed mechanisms remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines play an important role in Plasmodium infection [28] and the levels of cytokines are associated with the expression of Tim-3 [29]. Thus, the presence of IL-2, IL-4, IL-6, IL-9, IL-10, IL-22, TNF-α, and IFN-γ in the mouse sera at days 4, 9, 11, 13 and 14 p.i.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results have been observed in vivo by using a placenta-specific Atg7 (essential for autophagy) conditional knockout mouse model [ 68 ], which results in autophagy deficiency accompanied by poor placentation and elevated maternal blood pressure, suggesting its correlation with the pathophysiology of PE. Notably, both Gal-3 and Gal-9 have been implicated in the control of autophagy, acting as negative (Gal-3 [ 69 ]) and positive (Gal-9, mediated by polyLacNAc recognition [ 70 , 71 ]) modulators, respectively. These findings are in agreement with our observation that SHRSP implantations exhibited decreased Gal-9 and upregulated Gal-3 levels already at the onset of the disease and reduced polyLacNAc presentation (LEA staining) in placental compartments, which would possibly lead to impaired autophagy und thus cellular stress.…”
Section: Discussionmentioning
confidence: 99%